Constructing Religious Tolerance in Popular Digital Discourse: A Barthesian Semiotic Reading of Interfaith Representation in Indonesian YouTube Podcasts - Diva Raisa Zananda; ade masturi (2 issues per year (June and December), 2025)
This study examines how religious tolerance is constructed and articulated within popular digital discourse through a semiotic analysis of interfaith representation in Indonesian YouTube podcasts. The purpose of this research is to explore the layers of meaning embedded in a widely circulated podcast episode featuring six religious leaders from different faith traditions who engage in public dialogue during a shared religious celebration. Grounded in a qualitative descriptive approach and informed by a constructivist paradigm, the study employs Roland Barthes’ semiotic framework to analyze denotative, connotative, and mythical meanings conveyed through visual symbols, verbal interactions, and narrative structures within the selected digital content. Data were collected through non-participant observation, transcription of audiovisual material, and document analysis, allowing for an in-depth interpretation of signs and symbols that shape the representation of interfaith relations. The findings reveal that, at the denotative level, religious tolerance is signified through the visible presence of diverse religious attributes and equal participation among faith representatives. At the connotative level, tolerance is constructed through dialogic exchanges characterized by mutual respect, openness, and acknowledgment of difference without antagonism. At the mythical level, these representations reproduce and reinforce the national ethos of Bhinneka Tunggal Ika as a unifying cultural narrative that frames religious diversity as a shared moral and social ideal. The significance of this study lies in its contribution to scholarship on religion and digital media by demonstrating how popular platforms function as sites of meaning production where religious identities and values are symbolically negotiated and normalized. By situating interfaith representation within the dynamics of popular digital discourse, this research offers insight into the role of media in shaping contemporary understandings of religious coexistence in multicultural societies.